COVID-19 Pandemic: Impact on World Politics - M. M. Lebedeva (Vestnik MGIMO-Universiteta)
The COVID-19 pandemic has swept the world, affecting all socio-economic and political spheres. Over two years of the pandemic, numerous studies have examined many of its aspects. However, there is no comprehensive understanding of how the COVID-19 pandemic has affected and will still affect world politics.The article's research question is: how has the COVID-19 pandemic affected world politics in general? The article To understand the world political consequences of the COVID-19 pandemic, the following parameters were analyzed: 1) the impact of the pandemic on the (mega)trends of world political development globalization / de-globalization, integration/ disintegration, democratization / de-democratization, 2) the political organization of the world, which includes three primary levels: a) the principles of the Westphalian system, the main of which is the principle of sovereignty; b) the system of interstate relations; c) the political systems of individual states. The choice of these analysis parameters is explained in the article.States have used various strategies to deal with the pandemic, directed towards isolationism. At the same time, the polarization of the population increased. The system of interstate interaction has not fundamentally changed despite the difficulties that have arisen. The processes of de-globalization have intensified due to the policy of states towards isolationism. At the same time, globalization understood as transnationalization, manifested itself in the active use of digital communication technologies in various fields, including at the international (transnational) level. In turn, the megatrend of democratization was expressed in the activities of volunteers, the opening of access to performances, lectures, museum exhibits on online platforms.In general, it is shown that the world's political organization has not undergone significant changes as a result of the global crisis caused by the COVID-19 pandemic. Because of the pandemic, the trends that emerged even before it began have continued and intensified. At the same time, the rapid development of previously formed processes has led to a sharp increase in social, economic, and political contradictions, and as a result – polarization on many grounds in world politics, which creates a potential danger of conflict development.